Gift Baskets for South Asia: Nuclear Risk Reduction and Crisis Management - Amber Jamil; Megan Goyette (International Journal of Nuclear Security, 2022)
Gift Basket diplomacy is an interest-based approach to negotiation that encourages voluntary commitments as incentives for cooperation. International diplomats used this approach during the Nuclear Security Summits (NSS), and it is the new standard for international cooperation. This model was successfully replicated in climate talks and led to a global effort to combat climate change. The use of house presents, and gift baskets encourages leadership and team building, to excel beyond intractable consensus-based stalemates. The Gift Basket Diplomacy model may reduce South Asia’s nuclear risk and enhance crisis management by increasing diplomatic efforts during regional party talks and cooperative engagements, by keeping negotiators on a focused path to substantive counterterrorism and border security cooperation.
Keywords: South Asia; Diplomacy; Multi-Party Talks; Nuclear Security Summits; Centers of Excellence; Pakistan; India; Technical Cooperation; Nonproliferation